Ožidaemye paradoksy v poslednem stihotvorenii G. R. Deržavina "Reka vremen v svoem stremlen'i ---" - Litvina, A. F. (Slavistična revija, 2016)
The paper demonstrates the connection between the structure and the content of the last poem of Gabriel Derzhavin and its formula dating back to the works of Herodotus. This formula was used on a regular basis in historiographical and didactic works as well as in legal texts of the Middle Ages and the early Modern period. It was especially consistently used in wills, which is highlighted in Derzhavin's poem Reka vremen ("Time's river").
Keywords: "Reka vremen v svoem stremlen'i ---"; 19.st.; 19th century; Deržavin, Gavril Romanovič, 1734-1816; literary formula; medieval historiography; predsmrtna pesem; ruska književnost; ruska poezija; Russian literature; Russian poetry; srednjeveško zgodovinopisje